Screening of cherry leaf roll virus in Sambucus nigra plants in Ukraine - Mishchenko, L.; Dunich, A.; Dashchenko, A.; Kozub, N.; Hlushchenko, L. (Quarantine and plant protection, 2022)
Goal. Cherry leaf roll virus (CLRV) infects naturally a wide range of herbaceous and woody plants, different species of trees, shrubs, horticultural, ornamental, weed plants and causes significant economic losses in many hosts and countries. CLRV on elderberry species was reported in Europe, USA, Iran and North America. Recently this virus has been detected in sour and sweet cherry fruit orchards in Ukraine. Testing of other hosts than Prunus was performed in Ukraine only recently. The aim of the study was to test the black elderberry plants (Sambucus nigra L.). for the presence of CLRV in the Poltava region and Kyiv regions. Methods. Sampling was carried out in the summer–autumn period in 2019—2021 in the territories of the Poltava and Kyiv regions and in Kyiv city. Samples of healthy elderberry plants were also analyzed. Visual diagnostics, enzyme-linked immunosorbent assay in DAS-ELISA modification, total RNA extraction, RT-PCR with primers for a 412 bp fragment of the 3’ untranslated region of the CLRV genome, and statistical data analysis were used in this research. PCR products were separated on an 1.5% agarose gel. Commercial CLRV preparations were used for positive controls in DAS-ELISA. Results. Thirty three elderberry samples with symptoms of leaf rolling and mosaics of varying degrees were selected in the territory of the Poltava and Kyiv regions and in Kyiv city in 2019 and 2021 and used in the study. ELISA and RT-PCR results showed that 82% of the tested black elderberry samples were infected by CLRV. Conclusions. The presence of CLRV, its harmfulness for elderberry plants, and Sambucus potential to serve as a reservoir for the virus indicate the necessity of testing a wider range of plant species for сherry leaf roll virus in Ukraine.